Can social protection promote women’s and girls’ climate resilience? - CGIAR Gender Equality Initiative (CGIAR Initiative on Gender Equality, 2023)
After two weeks of debate at COP28, the message is clear that climate change is hitting hardest some of those already most vulnerable and rapidly exacerbating inequalities, including gender inequality. Climate action is urgently needed – at scale, and with a gender lens. In the CGIAR Initiative on Gender Equality, HER+, we have been accelerating research with partners around the world to understand the role that social protection programs in low- and middle-income countries can play in boosting women’s and girls’ climate resilience, as well as to explore which program designs are promising for this objective.